The Impact of Climate Change on Rice Production in Nepal - Rayamajhee, Veeshan; Guo, Wenmei; Bohara, Alok K. (Economics of disasters and climate change, 2021)
Using panel data from Nepal Living Standard Surveys (NLSSs) from 2003 and 2010, this study investigates the impact of climate change on rice production in Nepal. Specifically, we use stochastic frontier model and incorporate both technical inefficiency and spatial filtering technique to estimate the impact of increases in average and extreme rainfall and temperatures on annual rice production. Our central finding is that a 1°C increase in average summer temperature results in a 4183 kg reduction in rice production. However, we find no evidence of such impact for increases in extreme temperature days. On the other hand, although we do not find a direct link between increases in average monsoon rainfall and rice production, our results show that extreme rainfall variation hurts productivity. Moreover, we find that a large majority of agricultural households in rural Nepal practice technically inefficient production methods. Households in districts with higher road and river densities are more technically efficient despite climate challenges, which suggests that improved irrigation and market access are needed for climate adaptation.